2016
DOI: 10.1002/1873-3468.12487
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for dual receptor‐binding sites in Clostridium difficile toxin A

Abstract: TcdA (308 kDa) and TcdB (270 kDa) disrupt the integrity of the intestinal epithelial barrier and provide an environment favorable for Clostridium difficile colonization. Recent evidence suggests that entry of TcdA into cells is mediated by at least two domains. Here, we report the characterization of a second receptor-binding domain (RBD2) for TcdA. While both the isolated combined repetitive oligopeptides (CROPs) and RBD2 fragments are rapidly internalized into cells under physiologic conditions, only the CRO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…It appears that the CROPS domain contributes to but is not essential for host cell binding. Recently, Lambert and Baldwin (2016) reported that the region comprising residues 1361-1874 in TcdA is capable of binding and entering the host cell. Interestingly, a study by Olling et al (2011) observed that the presence of TcdA holotoxin does not affect the binding of TcdA 1-1874 to cells in competition assays.…”
Section: Cellular Receptors and Receptor-binding Domainsmentioning
confidence: 99%
“…It appears that the CROPS domain contributes to but is not essential for host cell binding. Recently, Lambert and Baldwin (2016) reported that the region comprising residues 1361-1874 in TcdA is capable of binding and entering the host cell. Interestingly, a study by Olling et al (2011) observed that the presence of TcdA holotoxin does not affect the binding of TcdA 1-1874 to cells in competition assays.…”
Section: Cellular Receptors and Receptor-binding Domainsmentioning
confidence: 99%